115k views
3 votes
-2(2x – 3) = - 6x +10
I need the steps and answer for doing this !

User Kieren
by
5.2k points

2 Answers

12 votes

Answer:

x = 2

Explanation:

-2(2x - 3) = -6x + 10 <- first, distribute the -2

-4x +6 = -6x + 10 <- subtract (the goal is to get the x's alone on one side)

-6 -6

-4x = -6x + 4 <- add

+6x +6x

2x = 4 <- divide by 2 to get the value of one x

2x/2 = 4/2

x = 2

Hope this helps :)

User Zhijian Lin
by
5.9k points
6 votes
-2(2x-3) = -6x+10
-4x + 6 = -6x +10
+6x -6 +6x -6
2x = 4
Divide by 2
x = 2
User ChopperCharles
by
5.3k points